Analisis Biaya dan Pendapatan Usahatani Cabe Rawit (Capsicum frutensces L.) di Desa Belangian Kecamatan Aranio Kabupaten Banjar Provinsi Kalimantan Selatan - Zulipah Mahdalena; Fenny Refiana; Aulia Rahmah (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
This research aims to determine the number of costs, Revenue, and Income of their Cayenne pepper farming in Belangian village Aranio sub-district. The method used is the survey method and observation techniques. The number of farmers using Purposive Sampling Method as many as 98 people, with Simple Random Sampling technique, so that 30 respondent farmers. The results of this study obtained a Production of 6955 kg/farmers. The average revenue obtained Rp.5.795,833/ farmers or Rp 5.738,44/ hectare. At the same time, the average income of farmers is Rp.3.033,991 or Rp.2.997,028/ hectare.